Surface area measurements of upper dental cast with different final impressionss - Reem Abdul Rahim (Journal of Baghdad College of Dentistry, 2013)
Background : surface area anatomy is a proportional point to the retention of complete denture, in past there was no quantitative method to evaluate the surface area, nowadays the size and shape of maxillary arch is measured by different electronically and mathematical devices. A study was therefore, undertaken to measure surface area of upper dental cast that was taken by different final impressions. Materials and methods: twenty patients were examined. All of them had a healthy palate with no singe of injury, trauma, or deformity. Casts were taken by three different final impressions; zinc oxide, additional silicon, and poly ether. And two different devices were used; the computerized one and the Aluminum foil measure. Age, sex, and shape of upper dental arch were also evaluated. Results: the results of this study showed that the use of different methods to measure the surface area of upper dental cast had a significant difference between the two different measurements, while there was no difference in the measurements between the different final materials. Age variable showed more significant difference between the first and second method than sex variable. Conclusion: data collected in the present investigation showed a highly significant difference in measurements between the computerized method and the direct foil method. Zinc oxide, silicon and poly ether materials showed no significant differences in readings.